Cost analysis of sialendoscopy for the treatment of salivary gland disorders in children. (February 2022) - Velasquez, Nathalia; Gardiner, Lauren; Ramprasad, Vaibhav; Shaffer, Amber; Jabbour, Noel; Stapleton, Amanda
Abstract: Introduction: Recent advances in Otolaryngology have changed the diagnosis and therapy for salivary gland disorders. Sialendoscopy-assisted surgery is a minimally invasive, conservative procedure for functional preservation of the affected gland. The goals of this study are to assess the indications, use, and outcomes of pediatric sialendoscopy at a tertiary pediatric institution as well as to analyze the direct cost related to the diagnosis and treatment of patients with sialolithiasis and Juvenile Recurrent Parotitis managed with sialendoscopy. Methods: Retrospective cohort study of pediatric patients undergoing diagnostic and/or therapeutic sialendoscopy at a tertiary level children's hospital between 2012 and 2020. Demographic, clinical, surgical variables and direct hospital costs 1 year before and after the sialendoscopy procedure were collected and analyzed. Results: Twenty-two pediatric patients were included. There was male predominance (59.3%). The most common indication for sialendoscopy was Juvenile Recurrent Parotitis. Average age of onset was 6.5 years for patients with JPR and 14.2 years for patients with sialolithiasis. All patients had an average of 4.5 episodes before the first procedure. 8 patients required repeat sialendoscopy for recurrent symptoms. Mean total hospital costs were significantly higher in patients with JRP 1 year before and after the sialendoscopy ($4308.8 vs. $3330) compared to patients with sialolithiasis. Costs of the sialendoscopy and related expenses including anesthesia and PACU cost were similar in both studied groups ($13, 506 vs. $13, 022.9). Complete resolution of symptoms was achieved in 14 patients with JRP and all patients with sialolithiasis. Conclusion: Sialendoscopy is a low-risk procedure that aids in the treatment for pediatric salivary gland disorders. The costs related to sialendoscopy are substantial and patients with JRP incur higher hospital preoperative and postoperative costs compared to patients with sialolithiasis.